Designing and Implementing a 3DOF Robotic Arm for Color Sorting and Object Identification Using Computer Vision Technology (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper focuses on designing a three-degree-of-freedom robotic arm for color sorting using computer vision technology.  It involves the use of a robotic arm composed of three joints and a gripper for grasping and manipulating objects. Each joint is actuated by a servo motor that is controlled by an Arduino microcontroller to control the angles of the joints and achieve the desired motion. The microcontroller relies on a camera to detect and analyze colors. The camera captures an image of the objects present in the designated area and converts it into digital data to be processed later by a computer. Then, the well-known (OpenCV) and (NumPy) library in the Python programming language is used to process this data and identify the colors. Once the color is determined, the corresponding Python command is executed through the Arduino microcontroller. That allows the robotic arm to move towards the designated location based on the identified color. Consequently, the arm grasps the detected object and places it in the appropriate position according to its color. The effectiveness of the proposed approach has been verified in real-time experiments.